International space law - Dunk, Frans G. von der (International law (Edward Elgar) ;, 2018)
The scholarly contributions discussed in this timely research review address the special realm of legal rules applicable to space activities and their terrestrial applications. Outer space is generally considered a 'global commons', so this review focuses on the international regime which is also the foundation of an increasing number of national space laws. Topics covered concern the development, character and structure of international space law, its relationship with national space law, and military and commercial aspects of space activities, including launching and satellite applications. This fascinating study provides a comprehensive overview of the most important matters relating to international space law and will be a valuable research tool for academics and practitioners alike.